The Influence of Intellectual Capital on Return on Asset and Return of Equity in Companies in Jakarta Islamic Monetary Policy Index in Indonesia - Mustika, Marlinda; Batubara, Maryam; Bi Rahmani, Nur Ahmadi (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study is entitled The Effect of Intellectual Capital on Corporate Financial Performance with Islamic Corporate Social Responsibility as an Intervening Variable in Companies Listed on the Jakarta Islamic Index for the 2019–2023 Period. The research object consists of companies listed on the Jakarta Islamic Index (JII), focusing on the variables of Intellectual Capital, Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Capital Employed Efficiency (CEE) in relation to financial performance, which is proxied by Return on Assets (ROA) and Return on Equity (ROE). This study aims to analyze the effect of Intellectual Capital on corporate financial performance and to examine the role of intellectual capital efficiency components in improving corporate profitability. The research employs a quantitative approach using purposive sampling. The data used are secondary data obtained from companies’ financial statements for the 2019–2023 period. Data analysis is conducted using regression analysis to examine the relationships among the research variables. The results indicate that Intellectual Capital has a significant negative effect on ROA and ROE. Human Capital Efficiency (HCE) has a significant positive effect on ROA and ROE. Structural Capital Efficiency (SCE) shows a positive effect on ROA but a negative effect on ROE. Meanwhile, Capital Employed Efficiency (CEE) has a significant positive effect on both ROA and ROE.